A Novel Model of Internal Combustion Engine for High Efficiency Operation of Hybrid Electric Vehicles and Power Systems - Overington, Shane; Rajakaruna, Sumedha (IEEE, 2014)
This article realizes a novel model of an internal combustion engine (ICE) based on its operating torque and speed for the purpose of designing new control strategies to optimize engine efficiency and performance in hybrid electric vehicles and power systems. The proposed model is developed such that it utilizes only a limited number of experimentally measured operating conditions of the internal combustion engine. Therefore it helps in minimizing the expensive and time consuming testing of the vehicle under a large number of operating conditions in comparison to other models. On the other hand, it is possible to utilise the model to determine a novel control strategy for fuel consumption reduction in plug-in hybrid electric vehicles (PHEV) and hybrid electric vehicles (HEV). This fuel consumption reduction is achieved through the use of the proposed model to predict the efficiency of operation of the ICE instead of the fuel utilization predicted by conventional models. In order to prove the accuracy of the proposed model, efficiency of operation of six known ICEs have been modelled and compared with three existing models utilizing larger numbers of experimental data. The errors in efficiency in comparison to known data are found to be within a reasonable range. The paper finally demonstrates the possible applications of the proposed model in high efficiency control of ICE in a model of the 2010 Toyota Prius developed using experimental data. The demonstration for the proposed model is in the form of a vehicular system however it is envisaged that this model has applications in hybrid power systems also.